THE URBANIZATION IN SEMARANG CITY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
ABSTRACT Thepurpose thispaper is to provide a broad overview of the recent patterns and trends of urban growth, and to discuss the relationship between urbanization, economic and population growth and environment in Semarang City. Over the last 20 years many urban areas have experienced dramatic growth, as a result of rapid population growth and as the world's economy have been transformed by a combination of rapid technological and political change. Centralistic type of development from New Era Government gives consequences in the formation of mega urbanization. As a geographic phenomenon, urbanization is seen as a continuumfrom community level until global level. In the cases of Semarang, there is much more than a doubling. Net migration in many cases contributes as much as two thirds of the population growth in these zones, whereas in the city cores, net migration contributes little to growth. The main factor which is influencing urbanization process in Semarang is the growth of service sector, especially informal activities. A comprehensive model suggests that urbanization in Semarang is influenced by structural and social demographic factors. So, the balance between managing urban discharges to environment and enhancing environmental resource capacity is key determinant of the sustainability of the development in Semarang and livabilitY in general Keywords : urbanization, population growth, mega urban, environmental, degradation, sustainability development